2019
DOI: 10.1159/000499483
|View full text |Cite
|
Sign up to set email alerts
|

Does Uterine Doppler Add Information to the Cerebroplacental Ratio for the Prediction of Adverse Perinatal Outcome at the End of Pregnancy?

Abstract: <b><i>Objective:</i></b> To evaluate whether the addition of the mean uterine arteries pulsatility index (mUtA PI) to the cerebroplacental ratio (CPR) improves its ability to predict adverse perinatal outcome (APO) at the end of pregnancy. <b><i>Methods:</i></b> This was a prospective study of 891 fetuses that underwent an ultrasound examination at 34–41 weeks. The CPR and the mUtA PI were converted into multiples of the median (MoM) and the estimated fetal weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 37 publications
1
20
1
2
Order By: Relevance
“…When early-onset FGR is suspected, the inclusion of uterine artery Doppler in the assessment has the advantage that it reflects placental insufficiency from the maternal side and captures the placental insufficiency secondary to pathophysiological mechanisms other than early defective trophoblastic invasion 15 . There is expert consensus that abnormal uterine artery Doppler is a diagnostic criterion for early-onset FGR, while, for late-onset FGR, there was agreement between only 55% of experts and it was therefore not included as a diagnostic criterion 9,16 . While it could be speculated that uterine artery Doppler has the potential confounding characteristic of being useful both for prediction of outcome and for diagnosis, it may be argued that its prediction capacity overshadows its diagnostic performance.…”
Section: Introductionmentioning
confidence: 99%
“…When early-onset FGR is suspected, the inclusion of uterine artery Doppler in the assessment has the advantage that it reflects placental insufficiency from the maternal side and captures the placental insufficiency secondary to pathophysiological mechanisms other than early defective trophoblastic invasion 15 . There is expert consensus that abnormal uterine artery Doppler is a diagnostic criterion for early-onset FGR, while, for late-onset FGR, there was agreement between only 55% of experts and it was therefore not included as a diagnostic criterion 9,16 . While it could be speculated that uterine artery Doppler has the potential confounding characteristic of being useful both for prediction of outcome and for diagnosis, it may be argued that its prediction capacity overshadows its diagnostic performance.…”
Section: Introductionmentioning
confidence: 99%
“…A multicenter prospective study showed that in the low-risk population (n = 804) at term, too, there was a six-fold increase in the rate of emergency surgical delivery due to intrapartal fetal distress as well as a higher rate of APO in cases with a CPUR < 10th percentile, even though the predictive power of the CPUR was moderate at best 43 . Morales-Rosello et al, however, could not determine an added predictive value of the CPUR with regard to APO when compared to the CPR in the low-risk population between 34 + 0 – 41 + 0 WG (n = 891) 44 .…”
Section: Fetomaternal Doppler Ultrasoundmentioning
confidence: 94%
“…Aus der Überlegung heraus, die mütterliche Seite der Plazenta in die Doppler-Sonografie-basierende APO-Risikoabschätzung und fetale Zustandsbeschreibung zu integrieren, gehen erste Studien hervor, welche die Rolle der zerebroplazentar-uterinen Ratio (CPUR = CPR/mUtA-PI) ( Abb. 2 ) im High- und Low-Risk-Kollektiv beleuchten 42 , 43 , 44 . Macdonald et al konnten erstmalig an einem Kollektiv von n = 347 Patientinnen zeigen, dass die CPUR die stärkste Assoziation mit Indikatoren für eine späte, milde Plazentainsuffizienz aufwies und im Vergleich zur CPR und/oder mUtA-PI allein mehr Fälle von FGR (BW < 3.…”
Section: Fetomaternale Doppler-sonografieunclassified
“…Two studies investigating the role of uterine artery (UtA) Doppler for the prediction of adverse perinatal events in third-trimester AGA fetuses also demonstrated poor test performance 100,101 .…”
Section: Current Evidence On Doppler Assessment Prior To and During Labor In Appropriately Grown Fetusesmentioning
confidence: 99%
“…The use of biomarkers reflective of poor placental function (i.e. sFlt-1, PlGF or the sFlt-1/PlGF ratio) in combination with fetal Dopplers has been evaluated in two prospective observational studies in uncomplicated pregnancies between 35 +0 and 36 +6 weeks or beyond 36 weeks of gestation [101][102][103] . However, the addition of placental biomarkers did not yield an improvement in test performance for screening of adverse perinatal outcomes.…”
Section: Current Evidence On Doppler Assessment Prior To and During Labor In Appropriately Grown Fetusesmentioning
confidence: 99%